2009
DOI: 10.1037/a0016963
|View full text |Cite
|
Sign up to set email alerts
|

Trichotomous processes in early memory development, aging, and neurocognitive impairment: A unified theory.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link IN PRESS: Psychological Review AbstractOne of the most extensively investigated topics in the adult memory literature, dual memory processes, has had virtually no impact on the study of early memory development. We remove the key obstacles to such research by formulating a trichotomous theory of recall that combines the traditional dual processes of recollection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
190
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(200 citation statements)
references
References 174 publications
(340 reference statements)
4
190
1
5
Order By: Relevance
“…The true recall rates were not as consistent with our predictions as we would have liked, but this may simply be due to the fact that the tasks are reflecting different processes: recall tasks require more reconstructive processing whereas recognition tasks may rely more on judgments of familiarity (for a more detailed consideration of differences between recall and recognition, see Brainerd, Reyna, & Howe, 2009). Indeed, it is not unusual to find differences of this sort between recall and recognition tasks for lists varying in valence (e.g., Howe, 2007;Howe, Candel, Otgaar, Malone, & Wimmer, in press).…”
Section: Accuracycontrasting
confidence: 38%
“…The true recall rates were not as consistent with our predictions as we would have liked, but this may simply be due to the fact that the tasks are reflecting different processes: recall tasks require more reconstructive processing whereas recognition tasks may rely more on judgments of familiarity (for a more detailed consideration of differences between recall and recognition, see Brainerd, Reyna, & Howe, 2009). Indeed, it is not unusual to find differences of this sort between recall and recognition tasks for lists varying in valence (e.g., Howe, 2007;Howe, Candel, Otgaar, Malone, & Wimmer, in press).…”
Section: Accuracycontrasting
confidence: 38%
“…An interesting question for further study is whether encoding processes that highlight attention to similarity may strengthen gistbased memory representations in older adults, and in turn lead to preserved memory performance. It also may be that older adults have a "default mode" of using gist-based encoding (Brainerd et al, 2009;Koutstaal & Schacter, 1997), and can thus benefit when attending to similarities among encoded stimuli. Providing initial support for this notion, analyses of the relation between task ratings at encoding and memory performance revealed that in older but not in younger adults, increasing similarity ratings were associated with increasing rates of recollection.…”
Section: Beneficial Effects Of Attending To Distinctivenessmentioning
confidence: 99%
“…Conversely, based on data suggesting a reduced ability among older adults to associate stimuli with their distinctive stimulus features (Naveh-Benjamin, 2000) as well as a reduced ability to encode unique memory representations (Stark et al, 2013;Toner et al, 2009;Wilson et al, 2006), we hypothesized that recollection would not be modulated by encoding task in older participants. Given prior work demonstrating that older adults preferentially rely on gist-based memory (Brainerd, Reyna, & Howe, 2009;Koutstaal & Schacter, 1997), we also explored an alternative hypothesis that in older adults attending to similarity may lead to higher rates of recollection than attending to distinctiveness to the extent that processing similarity favors the formation of gist-based memories.…”
mentioning
confidence: 99%
“…with a judgment operation that assesses the products of reconstruction (e.g., Brainerd, Payne, Wright, & Reyna, 2003;Brainerd, Reyna, & Howe, 2009;Brainerd, Wright, Reyna, & Payne, 2002;Reyna & Mills, 2007; also see Barnhardt, Choi, Gerkens, & Smith, 2006). Although there are numerous dual-process conceptions of recognition (e.g., Atkinson & Juola, 1973, 1974Atkinson & Westcourt, 1975;Gillund & Shiffrin, 1984;Horton, Pavlick, & Moulin-Julian, 1993), this is not the case with recall.…”
mentioning
confidence: 97%
“…There are a number of other reasons to expect that the phenomenological experience of false recall may be less vivid than that of false recognition. First, according to dual-recall theory (Barnhardt et al, 2006;Brainerd et al, 2009;Payne et al, 1996), early output is dominated by direct access to verbatim traces and recollective phenomenology, but later output is dominated by reconstruction from gist and nonrecollective phenomenology. Intrusions of semantic associates, in both standard and DRM recall, occur chiefly at the end of output sequences (e.g., Brainerd, Reyna, Harnishfeger, & Howe, 1993;Payne et al, 1996;Roediger & McDermott, 1995), suggesting that they are reconstructions not accompanied by recollective phenomenology.…”
mentioning
confidence: 99%